Designing prototype system for academic information service with Cloud Computing basis - Sutedi Sutedi; Arman Suryadi Karim (Politeknik Negeri Lampung, 2014)
Academic service system is one of the supporting elements in education in high school or universities. Despite the rising awareness of the usefulness of the IT based academic system, some education institutions do not have the ability of developing and implementing the system, especially due to the limited financial condition. The development of cloud computing based information system appears as a new paradigm in IT world which enable the school to implement IT based academic information system without investing big expenses of IT tools. The research is to learn the design of architecture system and prototype system of the supporting software for the school academic services. The result of this study would be the computer software to implement at school to improve the academic system especially those schools with limited financial condition and resources in developing the systemKey words: academic service, cloud computing, IT services